Regenerated trees in farmers’ fields increase soil carbon across the Sahel - Bayala, Jules; Sanou, J.; Bazié, H.R.; Coe, R.; Kalinganire, A.; Sinclair, Fergus L. (Springer, 2020)
In the current debate on the role of increase soil carbon in addressing both climate change and food security, there is consensus that farmed lands have the higher potential provided the best management practices are implemented. In the Sahel where farms usually have few sparse old trees with declining soil fertility, there is an ongoing re-greening process with increases in tree cover for which there is still a dearth of quantified information on its impacts on soil properties. This research aimed at filling that gap. We sampled soil using a concentric zone design around individual trees of dominant species and at different soil depths (0–10, 10–30, 30–50 and 50–70 cm) in four Sahelian countries: Burkina Faso, Mali, Niger and Senegal. The results showed increase total carbon content of the top 0–10 cm soil, generally with high sand content (> 70%), ranged from 0.16 to 0.44% (mean 0.23%). Under trees it was a factor 1.04–1.47 higher than away from trees. Different tree species thrived in different ecological niches and had different impacts on soil properties, highlighting the need for site and species matching in restoration activities. These results suggest that increase vegetation cover in the Sahel is associated with an increase in soil total carbon and this trend is more pronounced on sandy soils.